(untitled) (Alternautas, 2016)
All victories are Pyrrhic, to a greater or lesser extent. That is, no victory is ever complete; victors always have to concede something to the vanquished. At the very least, for instance, those who emerge victorious from a political (or other) struggle either depend upon or, worse still, have to make do without the recognition on the part of the vanquished that they have indeed won. Either, that is, the losing side sign, metaphorically or otherwise, the equivalent of some kind of document of surrender, in which case they have retained the power to determine that the struggle is indeed at an end. And this retained power forces an acknowledgement, on the part of the winners, that their victory cannot be total even if the surrender is unconditional. Or, worse still, the losers do not sign such a document, either because they refuse to acknowledge defeat or because they will not or cannot acknowledge the victors and the legitimacy of their victory. In which case, symbolically and perhaps not just symbolically, the struggle continues and victory remains elusive for the victors.